Analisis Sistem Informasi Akuntansi Penjualan Tunai pada PT Intidaya Dinamika Sejati di Kabupaten Jember - Amanda Ivon (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the implementation of the cash sales accounting information system at PT Intidaya Dinamika Sejati. The study applies a qualitative descriptive approach using data collection techniques including observation, interviews, and documentation analysis. The company implements an integrated Enterprise Resource Planning (ERP) system to manage sales transactions, control operational data, and generate financial reports. The cash sales system involves several interrelated functions, including sales, cash handling, warehouse, delivery, and accounting, supported by documents such as sales orders, delivery notes, and sales invoices. The findings indicate that the implementation of the cash sales accounting information system is generally consistent with the theoretical framework proposed by Mulyadi, particularly in terms of procedural stages and segregation of duties. However, the company has developed additional procedures as operational adjustments to strengthen internal control and monitoring mechanisms. The study also reveals that in certain conditions with short lead times, goods are released before delivery notes and sales invoices are issued, although the transactions are subsequently completed through the ERP closing process. These findings indicate the need for improved synchronization between operational execution and administrative documentation to enhance the reliability and effectiveness of accounting information systems.
Approved by Teddy
Keywords: Accounting Information System; Cash Sales; Enterprise Resource Planning (ERP); Internal Control; Segregation of Duties.